OPTIMALISASI PELAYANAN SEBAGAI UPAYA MENCAPAI RUMAH SAKIT STANDAR INTERNASIONAL JCI - Anak Agung Istri Putri Wahyuni (Jurnal Manajemen dan Bisnis, 2013)
of this research is “Service Optimization to Achieve International StandarHospital JCI”. Background : Global competition coused the change of health serviceparadigm and Bali as the main tourism research.Method and Result : The object of this research to know the optimization steps,related factor and this implication. The research use qualitative descriptive located in RSUPSanglah. Collecting data is carried out with deep interview to informant, those are outpatient, in patient and emergency. The result of research shown that JCI service standardoptimization is not fully done yet, mainly for the facility standard, human resources andcommunity participation.The conclusion of this research axplain that JCI service standard optimization consistof : socialization, implementation and evaluation with paying attention on internal factor,such as : facility, human resources, leadership and governance. While, eksternal factor arepatient and community participation, and related institution. Optimization impact to patientand RSUP Sanglah itself. The impact lead to increasing of patient demand, especially againsto service quality of RSUP Sanglah.Keywords : service optimization, internasional standar hospital